Pooled Testing for SARS‐CoV‐2 in Hospitalized Patients. Issue 9 (20th July 2020) - Mastrianni, David; Falivena, Richard; Brooks, Timothy; McDermott, Brian; Tan, Josenia; Vandell, Richard; Holland, Michael
Abstract : Viral testing for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), particularly early in the COVID‐19 pandemic, was limited by supply of reagents. We pooled nasopharyngeal samples from patients at low risk of SARS‐CoV‐2 infection in groups of 3 for testing. Three weeks of testing using this strategy resulted in 530 patient tests in 179 cartridges; 4 positive test groups required the use of 11 additional cartridges with an overall positive rate of 0.8% in a low‐risk population. This strategy resulted in the use of 340 fewer cartridges than if each test were performed on one patient sample. Pooled testing of low‐risk populations allows for continued testing even when supplies are relatively scarce.